How classroom acoustics influence students and teachers: A systematic literature review - Jordi Mogas Recalde; Ramon Palau; Marian Márquez (OmniaScience, 2021)
Acoustics in schools have been studied during years, but nowadays there are more possibilities than ever before to introduce improvements. This study presents a systematic literature review determining what acoustic parameters are present in classrooms and how they affect both teachers and students. Following the analysis, we put forward a two-block classification: the physical parameters of the sound or noise in the classroom and the consequences of the acoustics on the people in the classroom. Advances in the design of learning spaces and the use of technologies ranging from devices and green material to advanced automation systems make it possible to direct acoustic solutions toward smarter learning spaces. This review also highlights the acoustic parameters to consider in smart classrooms (noise, reverberation, speech transmission and speech clarity) and the main effects of acoustics on teachers and students. Some conclusions and recommendations are drawn, but more research is needed in terms of school improvement considering acoustics influence and smart classrooms possibilities.